SAT0196 Stereologic measurement of inflammatory synovial membrane volume on mr images. (1st June 2001) - Savnik, A; Thomsen, HS; Nyengaard, JR; Bliddal, H
Abstract : Background: Manual outlining of the synovial membrane on MR images in inflammatory joint diseases is too time consuming for clinical use. Objectives: The purpose was to introduce a less time-consuming stereologic method for measuring synovial volume by MRI in inflammatory joint diseases. Methods: Post-contrast 3-D T1-weighted turbo gradient MR images of the finger (metacarpophalangeal and interphalangeal) joints (14 joints) were acquired from 11 patients with rheumatoid arthritis (n = 8) and reactive arthritis (n = 3). Manually outlined volume was taken as a gold standard and compared with stereologic volume estimation on transverse 1 mm thick slices. Results: The total volume of 154 finger joints was estimated. A significant correlation between manual and stereologic estimations of synovial volumes was found (Spearman rho = 0.71, P = 0.002). 95% limits of agreement were ± 5–6 ml (14 finger joints per patient). The time used for volume determination in a patient varied from 1–2.5 h by manual outlining and from 0.5–1 h by stereologic determination. Conclusion: Stereologic volume estimation can provide measures of synovial volumes comparable to the manual outlining method and is less time-consuming. Stereologic volume estimation seems to be a clinically useful method, especially if it is integrated in the MR unit?s workstation.